Critical speed and frequency behavior of rotating joined FG-CNTRC conical-conical shells. (1st September 2022) - Heidari-Soureshjani, Ali; Talebitooti, Mostafa; Pakravan, Isaac; Talebitooti, Roohollah
Highlights: The system is modeled as two individual rotating FG-CNTRC conical shells which are merged by pursuing matching conditions at their interfaces. Coriolis and centrifugal forces alongside with initial hoop tensions are taken into account to achieve rotation induced motion equations. Bifurcation of frequencies due to the Coriolis effects is observed. Augmentation of rotating speed could converge frequencies for different FG patterns. Difference between backward and forward frequencies plunges as the circumferential mode number soars. Abstract: This paper provides information on critical speed and frequency behavior of rotating joined functionally graded carbon nanotube reinforced (FG-CNTRC) conical-conical shells. Furthermore, frequency bifurcation as a consequence of rotational effects is investigated. The shell is assumed to be composed of an isotropic polymer matrix that is reinforced by uniformly or functionally distributions of carbon nanotubes (CNTs). The structure's kinematics originates from the first order shear deformation theory (FSDT). To derive spin-based motion equations, Coriolis and centrifugal forces together with initial hoop tensions are propounded through the Hamilton's principle. Moreover, matching and boundary conditions are ascertained to supplement the governing equations. To discretize the governing equations meridionally, the generalized differential quadrature (GDQ) technique is employed. After validity checking, some significant parameters like cones' angles, rotation speed, edge supports, CNT volume fractions and dispersion patterns that play effective roles on the critical speed and vibration characteristics are examined. It is revealed that by enhancing spinning speed, frequencies of different FG patterns converge. In addition, difference between backward and forward frequencies decreases as the circumferential mode number increases.